Salmonella in Swiss and Imported Retail Chicken Meat – A Cross-Sectional Study - Karen Barmettler; Lucien Kelbert; Jule Anna Horlbog; Nicole Cernela; Michael Biggel; Roger Stephan (Journal of Food Protection)
Non-typhoidal Salmonella enterica (NTS) are significant foodborne pathogens responsible for many cases of enterocolitis worldwide, with the increasing threat of antimicrobial resistance (AMR) posing a growing public health concern. Salmonella Infantis has emerged as a predominant multidrug-resistant (MDR) serotype, particularly in poultry. This study investigated the Salmonella prevalence in 200 chicken meat samples from Swiss retail stores. Six (3%) samples tested positive; all were imported, and the isolates were all identified as S. Infantis. Whole genome sequencing confirmed the presence of the pESI (plasmid of emerging S. Infantis) megaplasmid, which is associated with enhanced persistence, biofilm formation, and multidrug resistance. Statistical analysis revealed a significant correlation between Salmonella prevalence and imported, unlabeled products. These findings highlight the effectiveness of Swiss control measures in the poultry production but underscore the importance of maintaining consumer awareness to mitigate Salmonella transmission and MDR risks.